El siglo XX dominicano en Colombia: propuesta de una periodización histórica (2022)
In his biography of Camilo Torres, historian Walter Broderick (1996) describes the Order of Preachers as obscurantist, and its members as ignorant and living off the superstitious practices of the country’s most underprivileged classes. This statement serves as a pretext for the introduction to an exercise of historical analysis on the decline, disappearance and subsequent restoration of the Order of Preachers in Colombia. The aim is to propose a periodization of the order in the country during the twentieth century. From the confrontation of primary and secondary sources, it seeks to highlight the social and political dynamics that led, simultaneously, to the construction of the republic and the decline of the religious orders in the country. Afterwards, in a more extensive way, the process of restoration of the Order between 1881 and 1965 will be presented, through the three phases that have been identified.